Sustainability on Business, Innovation and Marketing: A Bibliometric Analysis - Zulkieflimansyah, Zulkieflimansyah; Khadafie, Muammar (Dinasti Publisher, 2024)
This research design uses A bibliometric for Systematic Literature REVIEW. we performed searches using specific phrases in Scopus databases, resulting in 736 papers retrieved solely from Scopus. Subsequently, we selectively examined studies aligned with our research objectives and removed any redundant data. Publications originating from book chapters, conference proceedings, and written in languages other than English were omitted from our dataset. These findings underscore a significant opportunity for future research endeavors to generate innovative insights within the field of marketing management. The identified topic represents a crucial issue in supporting the sustainability of small and medium enterprises worldwide, given the lack of comprehensive discussion by researchers. However, it's important to acknowledge the limitations of this study. The reliance solely on data from the Scopus citation index means that topics explored in this study may have been researched in other sources, potentially limiting generalizability. Moreover, the study's timeframe is limited to five years, resulting in a relatively homogeneous set of previous research topics and themes. Therefore, future research endeavors could enhance the applicability of this study by broadening the scope of data sources and problems investigated.